The value of CT coronary angiography for a comprehensive assessment of left circumflex artery in Kawasaki disease: 9 years of experience from a tertiary centerResearch in context - Manphool Singhal; Rakesh Kumar Pilania; Abarna Thangaraj; Himanshi Chaudhary; Anjani Gummadi; Raghuraman Soundararajan; Sathish Loganathan; Arun Sharma; Aman Gupta; Sagar Bhattad; Ankur Kumar Jindal; Pandiarajan Vignesh; et al. (Elsevier, 2024)
Summary: Background: Transthoracic echocardiography (TTE) has traditionally been the primary method for coronary imaging in children with Kawasaki disease (KD). We aimed to evaluate coronary artery lesions (CALs) of the left circumflex artery (LCx) in KD on computed tomography coronary angiography (CTCA). Methods: Over a 9-year period (November 2013-December 2022), 225 children with KD underwent radiation-optimized CTCA on a 128-slice dual-source platform. TTE was performed on the same day, or a day prior or after CTCA. Findings: On CTCA, LCx CALs were seen in 41/225 (18.2%) patients. However, TTE detected CALs in only one third of these patients [15/41 (36.6%)]. CTCA showed 47 LCx CALs in 41 patients-aneurysms in 39 patients (40 fusiform, 2 saccular; 7 giant aneurysms), stenoses in 3, and thrombosis in 2. Thromboses and stenoses were both missed on TTE. Proximal LCx aneurysms were seen in 39 patients-of these, 12 had distal extension. Six patients had distal LCx aneurysms without proximal involvement and 2 non-contiguous multiple aneurysms. Four (9.75%) patients had isolated LCx involvement. Based on CTCA findings, treatment protocols had to be modified in 3/41 (7.3%) patients. Interpretation: This study highlights anatomical findings of LCx involvement in KD. Isolated LCx CALs were noted in 4/41 (9.75%) patients. TTE alone proved inadequate for LCx assessment in children with KD. With abnormalities detected in 18.2% of cases, including those missed by TTE, CTCA emerges as an essential imaging modality. The findings have implications for treatment planning and follow-up strategies in children with KD. Funding: None.